Young people's expressed needs for Comprehensive Sexuality Education in Ecuadorian schools. Issue 1 (2nd January 2018) - Castillo Nuñez, Jessica; Derluyn, Ilse; Valcke, Martin
Abstract: This study analyses the expressed sexuality education needs of young people from Azuay, a region of Ecuador characterised by a large proportion of young people whose parents have migrated abroad, a group often considered at risk to developing of sexual health problems. Multi-stage stratified cluster sampling was used to recruit young people aged 11 and 19 years to the study. The expressed needs of participants were analysed in relation to gender, parents' migratory status, age and geographical location. Survey findings revealed that young people expressed high needs with respect to the different components of Comprehensive Sexuality Education: gender roles, sexual and reproductive health, sexual citizenship, pleasure, violence, diversity and relationships. Ordinal regression analyses revealed few significant differences in relation to socio-demographic variables, which was surprising, in particular, with respect to the group of young people with migrating parents. Given the high levels of expressed needs, the findings carry important implications for the design and implementation of future sexuality education programmes.